WINNOWING THE GRAIN: AFFECTIVE PROBLEMS OF ORAL CORRECTIVE FEEDBACKSS IN SPEAKING CLASS IN EFL/ESL CONTEXT - Didik Hartono (Erudio Journal of Educational Innovation, 2021)
The study reviews some articles associated with the effects of oral corrective feedbacks, in affective domain, particularly in the form of affective problems. The data were retrieved from the journal database and selected by using inclusive and exclusive criteria in the systematic review, which were consisted of eleven projects conducted in both EFL and ESL classrooms in some countries. Results demonstrated positive perspective toward oral corrective feedbacks and the usefulness. All the projects admitted that it helped students to be self-reflective on their proficiency, helped to notice their error, and even in a certain case, helped to motivate students. However, simultaneously, it also caused some affective problems such as embarrassment, judgment, overthinking, resentment, worry, self-doubting, losing face, lowering confidence, anxiety, frustration, and withdrawal from future participation. We hypothetically believed that the affective problems are highly affected by the students’ age and maturity, perception, awareness of proficiency level, number of corrective feedbacks, and techniques while delivering the correction. Based on the results, it is suggested that the teacher should consider those aspects. Moreover, I realized that the discussion on oral corrective feedbacks pertinent to the affective domain have been understudied, thus some gaps can be filled out.